Роль перевода в становлении поэтики раннего украинского модернизма начала ХХ в. - Лесная, Галина (Przekłady Literatur Słowiańskich, 2021)
The development of modernism in the history of Ukrainian literature at the beginning of the 20th century was accompanied by a discussion in which the younger generation of writers opposed the conservative attitudes of the elders. The variety of artistic trends of that time led to the complexity of defining many aspects of the formation of modernism, including the question of the chronological framework of Ukrainian modernism as a phenomenon, as well as the origins of the ideological shift in Ukrainian culture of the late 19th and early 20th centuries. The task of mastering the new content of contemporary “foreign” literature was set by the literary groups “Moloda Muza” and “Ukrayins’ka hata”, who turned the development of the poetics of modernism into their aesthetic credo. It is important to determine what role literary translation, that Ukrainian writers in the early 20th century attached great importance, played in this process.